The Effect Of Political Connections, Transfer Pricing, and Firm Size On Tax Avoidance Practices - Rino Rinatza Zain; Sri Wahyuni Widiastuti (Universitas Serang Raya, 2024)
Several companies engage in tax avoidance, a strategy aimed at circumventing tax expenses. Within this study, tax avoidance is quantified through Cash ETR (Effective Tax Rate). The objective is to empirically elucidate the impact of political affiliations, transfer pricing, and company size on tax avoidance among mining firms listed on the Indonesia Stock Exchange (IDX) from 2018 to 2021. Employing a purposive sampling method, 113 samples were meticulously chosen to represent the population. Utilizing multiple linear regression analysis, the research revealed that transfer pricing significantly influences tax avoidance practices, while political connections and company size do not demonstrate such an effect.